2016
DOI: 10.1017/psrm.2016.35
|View full text |Cite
|
Sign up to set email alerts
|

Self-Selection and Misreporting in Legislative Surveys

Abstract: This article discusses the methodological challenges of legislative surveys. Following an overview of different types of survey biases, the article argues that self-selection and misreporting are the most critical problems for legislative surveys. In order to identify the self-selection and misreporting biases, we compare the answers to a survey from Swiss members of parliament with their observed behavior in the parliament. The empirical analysis shows that the survey sample has a substantial misreporting bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 57 publications
1
17
0
6
Order By: Relevance
“…First, most of the relevant data were gathered through a parliamentary survey. Although this approach provides a comprehensive overview of the parliamentary demand for evaluations, survey data always entail methodical problems that question the analytical power of the sample (Bundi, Varone, Gava, & Widmer, 2016). In doing so, problems of self-selection and misreporting are likely to appear, even if the measurement errors should be distributed equally FIGU RE 4 Predicted probabilities to demand an evaluation for legitimation…”
Section: Res U Ltsmentioning
confidence: 99%
“…First, most of the relevant data were gathered through a parliamentary survey. Although this approach provides a comprehensive overview of the parliamentary demand for evaluations, survey data always entail methodical problems that question the analytical power of the sample (Bundi, Varone, Gava, & Widmer, 2016). In doing so, problems of self-selection and misreporting are likely to appear, even if the measurement errors should be distributed equally FIGU RE 4 Predicted probabilities to demand an evaluation for legitimation…”
Section: Res U Ltsmentioning
confidence: 99%
“…However, previous studies did not scrutinise whether the linkages between MPs and interest groups matter for legislative co-sponsorship. This study fills a gap by focusing on a specific legislative behaviour that can be observed directly and, thus, avoiding the methodological bias of MPs misreporting (Bundi et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when groups deliver policy-relevant information, they target parties which share their ideological preferences and policy positions. Linkages are established between likeminded groups and MPs (Hall and Deardorff, 2006:75): business groups predominantly support the legislative activities of MPs belonging to right parties, while public interest groups primarily help MPs from left parties to design workable policies (Otjes and Rasmussen, 2015;Gava et al 2016;Wonka 2017). The present study contributes to this literature by looking more deeply at the impact of MP-grous links on parliamentary evaluation practice.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…seating in a group's board) with interest groups. The register of interests is a rich source of observational data showing that the average number of interest ties per MP has more than doubled over the last decade, from 3.5 in 2000 to 7.6 in 2011 (Gava et al 2016). In sum, the Swiss parliament offers an ideal setting for investigating the influence of interest group advocacy on MPs' evaluations requests.…”
Section: Case Selectionmentioning
confidence: 99%